A network view on interbank market freezes - Silvia Gabrieli; Co-Pierre Georg (Deutsche Bundesbank, 2014)
We study the liquidity allocation among European banks around the Lehman insolvency using a novel dataset of all interbank loans settled via the Eurosystem's payment system TARGET2. Following the Lehman insolvency, lenders in the overnight segment become sensitive to counterparty characteristics and banks start hoarding liquidity by shortening the maturity of their interbank lending. This aggregate change in liquidity reallocation is accompanied by a substantial structural change that can best be characterized as a shrinking of the interbank network. Such a change in the network structure is consequential: banks with higher centrality within the network have better access to liquidity and are able to charge larger intermediation spreads. Therefore, we show the existence of a sizeable interbank lending channel.
Keywords: D85; E5; G1; G21; 330; interbank loans; network topology; financial stability